The effects of bank-specific and macroeconomic determinants on CASA ratio of listed joint stock commercial banks in Vietnam - Quynh Trang Nguyen; Le Duc Nguyen; Thi Hong Mai Tran (Cogent Business & Management, 2024)
This study aims to assess the situation of the Current Account and Savings Account ratio (CASA ratio) among listed joint stock commercial banks (JSCBs) in Vietnam. Analytical data sourced from the Financial Statements and Annual Reports of 27 banks over 6 years (2018 – 2023) reveals that the CASA ratio in the period surveyed is relatively low and exhibits significant variation across different groups. Employing panel regressions, including Pooled Ordinary Least Squares (OLS), Fixed Effects Model (FEM), Random Effects Model (REM) and Generalized Method of Moments (GMM), the research examines the factors influencing CASA ratio, with GMM proving to be the best-fitting model. The analysis indicates that profitability and bank size are significant determinants of the CASA ratio, whereas economic growth, inflation, and liquidity exert a negative impact on CASA. Moreover, empirical evidence regarding the influence of real interest rates and non-performing loan ratios on CASA among JSCBs in Vietnam was not found. These findings hold implications for JSCBs and policymakers, offering insights to enhance deposit mobilization in Vietnam's banking sector, thereby promoting efficient capital utilization and ensuring system stability in the future.Increasing the CASA ratio is one of the most important goals of commercial banks to reduce funding costs and enhance their competitive capacity. In this paper, we evaluate the current situation of the Current Accounting Savings Account ratio (CASA) of listed joint stock commercial banks in Vietnam. Using panel regressions employing techniques such as Pooled-ordinary least squares (OLS), fixed effects model (FEM), random effects model (REM), and Generalized Method of Moments (GMM), we examine the impact of factors on CASA ratio, with GMM demonstrating the best fit to the model. The findings are meaningful to both commercial banks and the policymakers, providing insights to stabilize deposit mobilization of Vietnamese commercial banks, thereby ensuring the efficient utilization and safety of capital within the banking system in the future.
Keywords: D04; E52; G21; 650; Current account andsavings account ratio; casa ratio; listed jointstock commercial banks; JSCBs; customer deposits